Genome-Wide Analysis of Allele-Specific Expression Patterns in Seventeen Tissues of Korean Cattle (Hanwoo) - Lim, Kyu-Sang (Animals (Basel), 2019)
SIMPLE SUMMARY: Allele-specific expression (ASE) is the biased allelic expression of genetic variants within the gene. Recently, the next-generation sequencing (NGS) technologies allowed us to detect ASE genes at a transcriptome-wide level. It is essential for the understanding of animal development, cellular programming, and the effect on their complexity because ASE shows developmental, tissue, or species-specific patterns. However, these aspects of ASE still have not been annotated well in farm animals and most studies were conducted mainly at the fetal stages. Hence, the current study focuses on detecting ASE genes in 17 tissues in adult cattle. In particular, we analyzed the monoallelic expression (MAE), which is a subtype of ASE where only one of two alleles are expressed. ABSTRACT: The functional hemizygosity could be caused by the MAE of a given gene and it can be one of the sources to affect the phenotypic variation in cattle. We aimed to identify MAE genes across the transcriptome in Korean cattle (Hanwoo). For three Hanwoo family trios, the transcriptome data of 17 tissues were generated in three offspring. Sixty-two MAE genes had a monoallelic expression in at least one tissue. Comparing genotypes among each family trio, the preferred alleles of 18 genes were identified (maternal expression, n = 9; paternal expression, n = 9). The MAE genes are involved in gene regulation, metabolic processes, and immune responses, and in particular, six genes encode transcription factors (FOXD2, FOXM1, HTATSF1, SCRT1, NKX6-2, and UBN1) with tissue-specific expression. In this study, we report genome-wide MAE genes in seventeen tissues of adult cattle. These results could help to elucidate epigenetic effects on phenotypic variation in Hanwoo.